Comparison of Antimicrobial Effectiveness of Orange and Lime’s Extracts on Aeromonas sobria and Aeromonas hydrophila - Nenni Dwi Aprianti Lubis; Sri Amelia; Era Yusraini; Zikrina Rahmi; Ridwan Balatif (Journal of Pure and Applied Microbiology, 2023)
Aeromonas bacteria are often found in aquatic environments and can be isolated from various types of fish. Globally, the incidence of infection by Aeromonas reached 0.6–76 cases per 1 million people. Orange and lime are generally used as cooking spices to get rid of the fishy smell in fish, and also have antibacterial effects. The study compared the antibacterial effectiveness of lime and orange extracts on two Aeromonas species; A. sobria and A. hydrophila. Bacteria Aeromonas may emerge from fresh tuna bought in traditional markets. Lime and orange extracts were prepared using the maceration method using 96% methanol as solvent. The extract concentrations used were 6.25%, 12.5%, 25%, and 50%. Antimicrobial sensitivity test was carried out using the Kirby-Bauer method. The bacterial inhibition zone test revealed that the effectiveness of extracts on both oranges and limes was higher for the bacteria A. hydrophila compared to A. sobria. It is known from the average diameter of the inhibition zone, which is larger on A. hydrophila compared to A. sobria, except for the extract with a concentration of 6.25% orange and 50% lime. In a comparison between extracts, lime extract was found to be more effective as an antimicrobial than orange extract, except at a concentration of 6.5% in the bacterial test A. sobria and 50% concentration in the bacterial test A. hydrophila. In general, lime is more effective as an antimicrobial than orange.